Global Pc5 geomagnetic pulsations of March 24, 1991, as observed along the American sector - Trivedi, N.B.; Arora, B.R.; Padilha, A.L.; DaCosta, J.M.; Dutra, S.L.G.; Chamalaun, F.H.; Rigoti, A. (My University, 1997)
Analysis of the globally coherent Pc5 geomagnetic pulsation event of March 24, 1991, from a chain of stations extending from the auroral oval to the equatorial region along the American sector, has shown unequivocal evidence on the enhancement of pulsation amplitude in the narrow equatorial band centered at the dip equator. The fine spatial structure of this equatorial enhancement, documented observationally for the first time, emphasizes the importance of an ionospheric component associated with enhanced Cowling conductivity. The presence of an ionospheric component is also indicated at mid-latitudes by the sharp increase in the amplitude of pulsations, more dominantly in the Y than in the X component, on the sunward side of the dawn terminator. The sunrise effect also causes a reversal of the sense of rotation of the wave polarization across the dawn terminator. Propagation of the magnetospheric inducted polar electric field to low and equatorial latitudes through the ionosphere is invoked to account for the equatorial enhancement and the sunrise effect seen in these Pc5 pulsations.
Keywords: Geomagnetic pulsations; American sector; Polar electric field; Pc5 pulsations